Risk Analysis of Ship Collision and Modelling of Oil Spill Trajectory Study Case : Dumai Port - Noor, Fariz Maulana; Handani, Dhimas Widhi; Muryadin, Muryadin; Sari, Dian Purnama; Wijaya, Rio Dwi Sakti; Prasetyo, Dimas Fajar; Setiyobudi, Nanang; Putra, Arfis Maydino Firmansyah; Malakani, Arga Iman; Afandi, Mohamad Imam (Department of Naval Architecture - Diponegoro University, 2025)
Dumai Port is a significant natural port in Sumatra, characterized by deep waters sheltered from waves and calm currents due to surrounding islands. It plays a crucial role in the export of Crude Palm Oil (CPO) and the operations of Pertamina's RU II, which are expected to increase, leading to a rise in ship traffic. In response to this growing vessel traffic, this paper analyzes ship collision frequency and models the dispersion of oil spills as a potential consequence. The ship collision analysis utilizes the Integrated Waterway Risk Assessment Program (IWRAP), combining vessel traffic data over a year with the port's bathymetric data. The analysis revealed a total collision frequency of 0.589766 across various scenarios, including head-on, overtaking, crossing, bending, and merging, which is considered acceptable as it falls below the threshold of one collision per year. Additionally, oil spill trajectory modeling was conducted using two types of oil and two wave heights. In the 2000 m³ oil spill modeling at a height of 0.5 m, the crude oil model showed 68.4% still floating, while the product oil model had 41.7% floating. In the 1.5 m modeling, the crude oil model had 29% floating, and the product oil model had 16.2% floating. Based on these results, the chosen cleanup methods include oil booms, skimming, and dispersants. Effective oil spill cleanup requires collaboration among various stakeholders to ensure the process is carried out efficiently and accurately.